2007
DOI: 10.1109/iccad.2007.4397237
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of RF circuits using combined circuit simulator-full wave field solver approach

Abstract: As technologies continue to shrink in size, modeling the effect of process variations on circuit performance is assuming profound significance. Process variations affect the onchip performance of both active and passive components. This necessitates the inclusion of the effect of these variations on distributed interconnect structures in modeling overall circuit performance. In this work, first it is shown through field-solver simulations that larger process variations lead to non-Gaussian PDFs (Probability De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…It is shown that the pdfs of equivalent circuit parameters such as the series inductance L and the series resistance R are non-Gaussian and correlated [4]. The same holds true for a general circuit model of the spiral inductor.…”
Section: Statistical Performance Analysis Of Microwave Amplifiersmentioning
confidence: 63%
See 1 more Smart Citation
“…It is shown that the pdfs of equivalent circuit parameters such as the series inductance L and the series resistance R are non-Gaussian and correlated [4]. The same holds true for a general circuit model of the spiral inductor.…”
Section: Statistical Performance Analysis Of Microwave Amplifiersmentioning
confidence: 63%
“…The steps involved in this methodology are described in detail in a previous work [4]. For the active part, random variations in gate oxide thickness, zero-bias threshold voltage reduction and reduction in channel length have been taken into account with appropriate correlations.…”
Section: Statistical Performance Analysis Of Microwave Amplifiersmentioning
confidence: 99%